1988
DOI: 10.1073/pnas.85.8.2753
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous and heterozygous deletions of the von Willebrand factor gene in patients and carriers of severe von Willebrand disease.

Abstract: Severe von Willebrand disease is characterized by undetectable or trace quantities of von Willebrand factor in plasma and tissue stores. We have studied the genomic DNA of 10 affected individuals from six families with this disorder using probes from the 5' and 3' ends of the vWF cDNA and with a probe extending from the 5' end into the central region. Southern blots of restriction endonuclease digests and gene dosage analysis measurements carried out with quantitative slot blots of undigested genomic DNA separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 19 publications
1
64
0
1
Order By: Relevance
“…HRM analysis was then carried out for 25 exons (number 4,6,8,9,11,12,16,17,19,20,21,23,25,30,34,35,36,38,39,40,41,44,46,48,51) in all patients. This is a mutation scanning technique that monitors the progressive change in fluorescence caused by the release of an intercalating DNA dye from a DNA duplex as it is denatured with marginal increases in temperature [18].…”
Section: Mlpamentioning
confidence: 99%
See 1 more Smart Citation
“…HRM analysis was then carried out for 25 exons (number 4,6,8,9,11,12,16,17,19,20,21,23,25,30,34,35,36,38,39,40,41,44,46,48,51) in all patients. This is a mutation scanning technique that monitors the progressive change in fluorescence caused by the release of an intercalating DNA dye from a DNA duplex as it is denatured with marginal increases in temperature [18].…”
Section: Mlpamentioning
confidence: 99%
“…VWD3 patients may develop alloantibodies against VWF as a consequence of their treatment with VWF/FVIII concentrates. Since this complication renders replacement therapy ineffective and may also be the cause of life threatening anaphylactic reactions, screening for homozygous large deletions, associated previously with the presence of alloantibodies [5][6][7][8] is highly recommended. Of late, we have reported a retrospective studies on the management of inherited VWD in Italy that included 66 VWD3 patients.…”
Section: Introductionmentioning
confidence: 99%
“…21 The Ͼ 110 type 3 VWD cases that have been genetically characterized show a range of VWF mutations, from large VWF deletions through a miscellany of null mutations to missense mutations that prevent VWF biosynthesis and secretion. Although initial studies of the infrequent cases of type 3 VWD developing alloantibodies to VWF showed an association with VWF deletion mutations, 22,23 there has been no systematic confirmation of this observation. 24 Type 1 VWD Type 1 disease comprises 65% to 75% of VWD cases in most series.…”
Section: Type 3 Vwdmentioning
confidence: 93%
“…The VWF gene sequence is replicated in part by a partial VWF pseudogene on chromosome 22. This evolutionary remnant recapitulates exons 23-34 of the VWF gene with 3% variance, a fact that significantly complicates the genetic analysis of this central region of the VWF gene.…”
Section: The Vwf Gene and Proteinmentioning
confidence: 99%
“…Large gene deletions appear to be an uncommon mechanism for vWD, seen primarily in patients with inhibitors to vWF (14,24,25). Missense mutations within the vWF A2 domain were recently identified in two patients with Type IIA vWD (26) and additional Type 11A patients may demonstrate other mutations in the same region (27).…”
mentioning
confidence: 99%